Superovulation Response, Embryo Recovery and Quality in Sahiwal Cows and Heifers - SIDDIQUl, M U; PANCHAL, M T; KAVANI, F S (The Indian Journal of Animal Reproduction, 2023)
Superovulation response, embryo recovery and quality in Sahiwal cows and heifers were studied in 12 animals divided in two grmips (Group A: 6 Sahiwal cows and Group B: 6 Sahiwal heifers). For induction of superovulation, FSH-P (Folltropin-V, Bioniche Animal Health, Canada, @ 200 mg per donor in 8 equally divided doses of 1.25 ml each) ,vas administered i.m. over four days at 12 hr interval, starting day 9 -11 post estrus. A single dose of PGF2a (lliren, lntervet,@ 5 ml) was given i.m. 48 hr after the first FSH injection, to bring the donors in heat. First A I was done 48 hr after PG injection, followed by two more inseminations at 12 hr intervals. On day 7 of first Al, all the donors were flushed for embryo recovery. Among 6 Sahiwal cows (Group A), only 3 (50.00%) responded to FSH treatment with the total number of CL to be 17 (5.67/donor) and a total of 10 (3 viable and 7 degenerated) embryos. The mean recovery of total and viable embryos (VE) for responded donors and overall were found to be 3.33 and 1.00 and 1.67 and 0.50 embryos per flush, respectively. All Sahiwal heifers (Group B) responded to FSH treatment with the total number of CL to be 50 (8.33/donor) and a total of 37 ( 18 VE; 2 UFO; 1 zona and · 16 degenerated) embryos. The mean recovery of total and viable embryos was found to be 6.17 and 3.00 embryos per flush, respectively. Sahiwal heifers (Group B) yielded comparatively higher number of mean ovulations (8.33) and embryos, both total (6. I 7) as well as viable (3.00), than those of the cows under Group A (3.17, 1.67 and 0.50, respectively). Based on the results obtained, it was concluded that since Sahiwal heifers had much better supersovulation response to gqnadotrophin treatment and higher recovery of total and viable embryos as compared to Sahiwal cows, heifers can be used as potential embryos donors.